CD4/CD8 ratio and CD8+ T-cell count as prognostic markers for non-AIDS mortality in people living with HIV. A systematic review and meta-analysis - Ron, Raquel; Martínez-Sanz, Javier; Herrera, Sabina; Ramos-Ruperto, Luis; Díez-Vidal, Alejandro; Sainz, Talía; Álvarez-Díaz, Noelia; Correa-Pérez, Andrea; Muriel, Alfonso; López-Alcalde, Jesús; Pérez-Molina, José A.; Moreno, Santiago; et al. (Frontiers in Immunology, 2024)
Background: In people living with HIV (PLHIV), the CD4/CD8 ratio has been proposed as a useful marker for non-AIDS events. However, its predictive ability on mortality over CD4 counts, and the role of CD8+ T-cell counts remain controversial.Methods: We conducted a systematic review and meta-analysis of published studies from 1996 to 2023, including PLHIV on antiretroviral treatment, and reporting CD4/CD8 ratio or CD8+ counts. The primary outcome was non-AIDS mortality or all-cause mortality. We performed a standard random-effects pairwise meta-analysis comparing low versus high CD4/CD8 ratio with a predefined cut-off point of 0.5. (CRD42020170931).Findings: We identified 2,479 studies for screening. 20 studies were included in the systematic review. Seven studies found an association between low CD4/CD8 ratio categories and increased mortality risk, with variable cut-off points between 0.4-1. Four studies were selected for meta-analysis, including 12,893 participants and 618 reported deaths. Patients with values of CD4/CD8 ratio below 0.5 showed a higher mortality risk (OR 3.65; 95% CI 3.04 -4.35; I2=0.00%) compared to those with higher values. While the metaanalysis of CD8+ T-cell counts was not feasible due to differences between studies, the systematic review suggests a negative prognostic impact of higher values (>1,138 to 1,500 cells/uL) in the long term.Conclusions: Our results support the use of the CD4/CD8 ratio as a prognostic marker in clinical practice, especially in patients with values below 0.5, but consensus criteria on ratio timing measurement, cut-off values, and time to event are needed in future studies to get more robust conclusions.